Haunted Dreams : Fantasies of Adolescence in Post-Soviet Culture - Kaminer, Jenny (Book collections on Project MUSE., 2022)
"This book analyzes representations of adolescence in Russian culture-including in prose, film, drama, and television-in the period since the end of the Soviet Union in 1991"--